2022
DOI: 10.1155/2022/3794021
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Validation of Significant Genes with Poor Prognosis in Pathologic Stage-I Lung Adenocarcinoma

Abstract: Background. Although more pathologic stage-I lung adenocarcinoma (LUAD) was diagnosed recently, some relapsed or distantly metastasized shortly after radical resection. The study aimed to identify biomarkers predicting prognosis in the pathologic stage-I LUAD and improve the understanding of the mechanisms involved in tumorigenesis. Methods. We obtained the expression profiling data for non-small cell lung cancer (NSCLC) patients from the NCBI-GEO database. Differentially expressed genes (DEGs) between early-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Etoposide, which targets TOP2A, has been approved for the treatment of small cell lung cancer, but there are currently no drugs for LUAD (48,49). Through various bioinformatics approaches, TOP2A has been identified as an independent factor affecting the prognosis of patients with LUAD (50)(51)(52)(53), whereas an increased TOP2A expression has also been identified as a potential risk factor for pathological stage I LUAD (54). Ciclopirox olamine and quercetin have also been demonstrated to exert tumor-suppressive effects via TOP2A in LUAD (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide, which targets TOP2A, has been approved for the treatment of small cell lung cancer, but there are currently no drugs for LUAD (48,49). Through various bioinformatics approaches, TOP2A has been identified as an independent factor affecting the prognosis of patients with LUAD (50)(51)(52)(53), whereas an increased TOP2A expression has also been identified as a potential risk factor for pathological stage I LUAD (54). Ciclopirox olamine and quercetin have also been demonstrated to exert tumor-suppressive effects via TOP2A in LUAD (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…During interphase, the ANLN protein is localized exclusively in the nucleus, whereas it becomes cytoplasmic during mitosis ( 30 ). Furthermore, ANLN has been identified as a poor prognostic marker associated with aggressive cancer phenotypes in multiple types of cancer, including bladder cancer ( 31 ), hepatocellular carcinoma ( 32 ), colorectal cancer ( 33 ), head and neck squamous cell carcinoma ( 34 ) and stage I LUAD ( 14 ). The present study demonstrated that high ANLN expression was significantly associated with clinical stage progression in patients with LUAD and that those exhibiting higher expression levels of ANLN had poorer prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…According to the expression profile of non-small cell lung cancer (NSCLC) obtained from the National Center for Biotechnology Information-Gene Expression Omnibus database (https://www.ncbi.nlm.nih.gov/geo/), UBE2T is one of the differential genes, and its prognosis risk ratio is the most remarkable. Its increase was identified as a potential risk factor for pathological stage I lung adenocarcinoma (LUAD) (79). Certain differential genes, particularly UBE2T, showed similar survival risks (80).…”
Section: Expression Of Ube2t In Cancermentioning
confidence: 99%